Metastasizing Bronchopulmonary Leiomyosarcoma. (22nd April 2015) - Livieratos, Speros; Fatakhov, Eddie; Ammar, Ali; Dillard, Thomas; Davis, Bruce
An otherwise healthy 55-year-old female, nonsmoker, was seen in pulmonary consultation for progressively worsening shortness of breath. She had undergone a complete hysterectomy 7 years prior for bleeding leiomyomas. On presentation, her initial chest X-ray showed a large right-sided pleural effusion with multiple pulmonary nodules. Two thoracenteses failed to reveal any cytologic abnormalities. Bronchoscopy revealed smooth, round, endobronchial lesions. Histologic examination showed features consistent with leiomyosarcoma. We present a rare case of a patient that initially had possible leiomyomas of the uterus surgically removed and years later presented with bronchopulmonary leiomyosarcoma.